Cast bronze vessels in the northern Adriatic region (c. 600 AD).: Rome and Ravenna, Nocera Umbra and Budakalász - Pinar Gil, Joan (Arheološki vestnik, 2022)
Although cast bronze vessels of the 6th–8th centuries are not recorded in particularly large numbers, their production and distribution provide a representative sample of the general economic trends and of the evolution of trade networks in the post-Roman Mediterranean. The geographical dissemination of these objects shows that at the turn of the 6th century, the northern Adriatic region became the main gateway of ‘eastern-style’ vessels into Central Europe and the Western Mediterranean. The region was thus replacing the Rome area as the main Western hub for redistributing this type of object. From the northern Adriatic area, several types of vessels were distributed both over land along the Po and Rhine valleys and through maritime routes connecting the Adriatic with Carthage and the Spanish Levant. The intrinsic features and the depositional contexts of the post-Roman cast bronze vessels suggest that they were manufactured according to different quality standards, which targeted different social milieus. Furthermore, mapping the distribution of the different quality standards reveals that each of them might have been distributed by different networks of merchants and unveils the impact of transportation costs on the final price of these products.